Sensorless control with multi-scalar transformation of five-phase IPMSM - Vyas, Deepak; Joy, Sahal Ibn Islam; Morawiec, Marcin; Kostro, Grzegorz; Sienkiewicz, Łukasz; Joshi, Nirav (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
This article proposes sensorless multiscalar control for a multiphase interior permanent magnet synchronous machine. The chosen parameters are estimated using an adaptive observer structure. In the proposed solution, the machine model vector form is in the stationary reference frame (), and transformation to () – the coordinate system is unnecessary to implement the proposed control structure. In the control structure, the nonlinear model linearization is based on demonstrated nonlinear variables transformation for ()() orthogonal planes. Using the proposed control technique, mechanical and electromagnetic subsystems are decoupled, which is the main advantage of this control structure. To provide a comparative analysis, the proposed multiscalar control structure is also compared with the existing multiscalar control scheme. Finally, the simulation and experimental results are demonstrated to validate the performance of the proposed control solution for a sensorless five-phase interior permanent magnet synchronous motor test setup.